FOOD IMPORT AND ECONOMIC RISK MANAGEMENT - Soatov Dostonbek Ibrohimovich, (Scholar Express Journals, 2024)
This study analyzes the economic risks associated with food import in Uzbekistan, exploring their impact on the national economy and identifying strategies to mitigate these risks. The research examines the fluctuations in global food prices, currency exchange rates, and their effects on domestic markets. Additionally, the paper reviews international experiences and best practices, particularly from the United States and the European Union, to understand the role of long-term strategies, technological innovations, and logistics improvements in managing food import risks. The findings emphasize the importance of effective governmental policies and the private sector's involvement in managing these economic risks. The study also highlights the significance of climate change and agricultural productivity issues as external factors influencing food security. Based on the analysis, the paper proposes practical recommendations to enhance food import risk management and improve national food security in Uzbekistan.
Keywords: Food Import; Economic Risks; Currency Fluctuations